Product Development Partnerships: Case studies of a new mechanism for health technology innovation - Mahoney Richard T (Health Research Policy and Systems, 2011)
Abstract There is a continuing need for new health technologies to address the disease burdens of developing countries. In the last decade Product Development Partnerships (PDP) have emerged that are making important contributions to the development of these technologies. PDPs are a form of public private partnerships that focus on health technology development. PDPs reflect the current phase in the history of health technology development: the Era of Partnerships, in which the public and private sectors have found productive ways to collaborate. Successful innovation depends on addressing six determinants of innovation. We examine four case studies of PDPs and show how they have addressed the six determinants to achieve success.